819 is the answer because thats how many visitors he got
Answer:
should be added to the given equation.
Step-by-step explanation:
Let a is added to the given equation.
According to the given condition,
![\dfrac{5x}{6}-4+a=\dfrac{x}{2}-4\\\\a=\dfrac{x}{2}-4+4-\dfrac{5x}{6}\\\\a=\dfrac{x}{2}-\dfrac{5x}{6}\\\\a=\dfrac{3x-5x}{6}\\\\a=\dfrac{-2x}{6}\\\\a=\dfrac{-x}{3}](https://tex.z-dn.net/?f=%5Cdfrac%7B5x%7D%7B6%7D-4%2Ba%3D%5Cdfrac%7Bx%7D%7B2%7D-4%5C%5C%5C%5Ca%3D%5Cdfrac%7Bx%7D%7B2%7D-4%2B4-%5Cdfrac%7B5x%7D%7B6%7D%5C%5C%5C%5Ca%3D%5Cdfrac%7Bx%7D%7B2%7D-%5Cdfrac%7B5x%7D%7B6%7D%5C%5C%5C%5Ca%3D%5Cdfrac%7B3x-5x%7D%7B6%7D%5C%5C%5C%5Ca%3D%5Cdfrac%7B-2x%7D%7B6%7D%5C%5C%5C%5Ca%3D%5Cdfrac%7B-x%7D%7B3%7D)
So,
should be added to the given equation.
Gross pay is the amount of money your employees receive before any taxes and deductions are taken out. For example, when you tell an employee, “I'll pay you $50,000 a year,” it means you will pay them $50,000 in gross wages.
Hope this helps!!
Answer:
I would say its 24 hope this helps
Answer:
D. (x - 2)(x - 2)
Step-by-step explanation:
x2 - 4x + 4 = x² - 2x - 2x +4
= x(x-2) - 2(x - 2)
= (x-2)(x-2)
HINT: - 2x +4 = -2 * x + (-2) * (-2) = -2 ( x -2)